Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1023/a:1011267005465
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Hydroxyapatite (HA) coatings have been used to improve implant fixation by promoting bone formation around the prosthesis. A macrophage response to HA particulates has been noted around loosened HA-coated prostheses. As biomaterial wear particle-associated macrophages are known to be capable of differentiating into osteoclasts that are capable of bone resorption, we examined whether particulate HA could similarly induce macrophage-osteoclast differentiation. HA-associated macrophages were isolated from granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…HA shows excellent biocompatibility and osteoconductivity due to its similar chemical and crystal resemblance to the mineral component of bone. On the surface of implants, the HA induces bony apatite formation 5 . It was found to promote bone growth when tested on dogs, indicating osteoinductive characteristic of HA.…”
Section: Introductionmentioning
confidence: 99%
“…HA shows excellent biocompatibility and osteoconductivity due to its similar chemical and crystal resemblance to the mineral component of bone. On the surface of implants, the HA induces bony apatite formation 5 . It was found to promote bone growth when tested on dogs, indicating osteoinductive characteristic of HA.…”
Section: Introductionmentioning
confidence: 99%
“…HA can promote the formation of bone-like apatite on its surface [9]. Polymers combined with HA are capable of promoting osteoblast adhesion, migration, differentiation and proliferation [10], especially useful for potential applications in bone repair and regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies of implant biomaterials have also suggested that attributes such as wear particle composition in prosthetic materials can modulate cellular activity by altering bonerelated gene profiles in vivo [23]. Recently, poly-methylmethacrylate (PMMA) particleassociated macrophages were shown to cause significantly more osteoclast formation and bone resorption than HA-associated macrophages, suggesting that particles derived from uncemented (HA-coated) implants are likely to induce less osteoclast formation and osteolysis than cemented implants [24]. These findings support the idea that a material compostion induced eefect on osteoclastic activity at the interface of prostheses may be a significant factor in the failure of orthopaedic implants.…”
Section: Introductionmentioning
confidence: 99%